Routledge Handbook of Chinese Medicine - Lo, Vivienne; Stanley-Baker, Michael (Taylor & Francis, 2022)
The Routledge Handbook of Chinese Medicine is an extensive, interdisciplinary guide to the nature of traditional medicine and healing in the Chinese cultural region, and its plural epistemologies. Established experts and the next generation of scholars interpret the ways in which Chinese medicine has been understood and portrayed from the beginning of the empire (third century BCE) to the globalisation of Chinese products and practices in the present day, taking in subjects from ancient medical writings to therapeutic movement, to talismans for healing and traditional medicines that have inspired global solutions to contemporary epidemics. The volume is divided into seven parts: Longue Durée and Formation of Institutions and Traditions Sickness and Healing Food and Sex Spiritual and Orthodox Religious Practices The World of Sinographic Medicine Wider Diasporas Negotiating Modernity This handbook therefore introduces the broad range of ideas and techniques that comprise pre-modern medicine in China, and the historiographical and ethnographic approaches that have illuminated them. It will prove a useful resource to students and scholars of Chinese studies, and the history of medicine and anthropology. It will also be of interest to practitioners, patients and specialists wishing to refresh their knowledge with the latest developments in the field. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license